THE DYNAMICS OF FLNKS INSURGENCY: EVOLVING STRATEGIES AND ITS QUEST FOR INDEPENDENCE - Mokhamad Saiful Farisin; Nazla Rahmanitya; Alvina Putri Fazha (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2025)
The quest for independence by the Front de Libération Nationale Kanak et Socialiste (FLNKS) from French colonial rule has been a longstanding endeavour. Despite three consecutive referendums in 2018, 2020, and 2021, the desired outcome has not been achieved. This study employs the CIA's stages of insurgency and a qualitative research method with data collected through a literature review to analyse the FLNKS's struggle for independence. The analysis places the FLNKS in the third stage of insurgency, specifically guerrilla warfare, with a focus on activities predominantly carried out by left-wing factions. The study identifies three pivotal factors contributing to the group's stagnation: internal support, external support, and information dominance. The results emphasize a decline in local support for the FLNKS, evident in the decreasing percentage of the Kanak population, which was in 2014. Additionally, the FLNKS's communication strategy primarily targets grassroots communities, while opposing groups, such as the Caledonie Ensemble, make effective use of modern media and technology. Furthermore, regional support from the Melanesian Spearhead Group and international assistance from the United Nations has been limited to technical and financial aid, falling short of realizing the FLNKS's aspiration for independence.